2005
DOI: 10.1103/physrevb.72.134407
|View full text |Cite
|
Sign up to set email alerts
|

Current-driven magnetic rearrangements in spin-polarized point contacts

Abstract: A new method for investigating the dynamics of atomic magnetic moments in current-carrying magnetic point contacts under bias is presented. This combines the non-equilibrium Green's function (NEGF) method for evaluating the current and the charge density with a description of the dynamics of the magnetization in terms of quasistatic thermally-activated transitions between stationary configurations. This method is then implemented in a tight-binding (TB) model with parameters chosen to simulate the main feature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 26 publications
(35 reference statements)
2
27
0
1
Order By: Relevance
“…An example of such generalized coordinates are magnetic degrees of freedom in spinpolarized nanowires. 4 The key finding ͓Eq. ͑24͔͒ is that the generalized self-consistent steady-state forces remain, in general, nonconservative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of such generalized coordinates are magnetic degrees of freedom in spinpolarized nanowires. 4 The key finding ͓Eq. ͑24͔͒ is that the generalized self-consistent steady-state forces remain, in general, nonconservative.…”
Section: Discussionmentioning
confidence: 99%
“…1 Nonetheless, a fundamental question about these forces was, until recently, not entirely clear: are they conservative or not, with arguments both ways. [1][2][3][4] The interest in these forces is partly physical and partly practical: in nanoscale conductors, where the current densities can be huge, these forces can, correspondingly, be large, opening up the question of how these corrections to ordinary interatomic forces affect the structure and functionality of atomic-scale devices. [5][6][7] Recently it was shown that current-induced forces are, indeed, not conservative, by evaluating explicitly their curl under steady-state conditions, 8 and that, therefore, these forces can do net work on the atoms around closed paths.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the parameters including the hopping matrix element provides a realistic choice for systems based on magnetic transition metals and their alloys. 50,51 In order to increase the band filling, we believe that different class of magnetic materials should be suggested, for example, alloying Fe͑Co͒ with impurities which can fill up the majority ⌬ 1 band.…”
Section: Resultsmentioning
confidence: 99%
“…The average force on the other hand contains, among other contributions, the familiar electron wind force [4][5][6][7][8][9]. In recent years the wind force has become the focus of renewed attention due to the realization that it is nonconservative [3,5,[10][11][12][13][14][15][16]. The importance of these nonconservative forces cannot be overestimated.…”
Section: Introductionmentioning
confidence: 99%